Studi Karakteristik Campuran AC-Base Menggunakan Batu Gunung Pura Lau Kecamatan Tikala - Dede Novit Senolinggi; Alpius; Charles Kamba (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
This study is to get character each of Laston base mixture using the Mount Pura Lau stone, Tikala District. The methodology in this study is to test each character of the sample to be tested for its, whether it is coarse aggregate, fine aggregate, filler, and asphalt. After testing each character, we will design the composition of the mixture for the manufacture of rough Laston Base (AC-BASE) specimens and obtain several variants of asphalt content, namely 4.5%, 5%, 5.55%, 6%, and 6.5%. After getting the composition, the test object will be made immediately. After the object has been made, it is time to test with Marshall test tool to obtain the residual Marshall Immersion / Stability Index (SMS) or the durability of the mixture using the optimum bitumen content. The results of the optimum asphalt content were 5.5%, MQ 906.88 Kg / mm and immersion index (IP) 96.06% which showed that met the requirements, namely 90% and meets the specifications of Bina Marga. So that it can be used as a recommendation to the regional government and local residents.